Ultrasound of the Hip Joint, Soft Tissues, and Nerves - Tagliafico, Alberto; Bignotti, Bianca; Rossi, Federica; Sconfienza, Luca Maria; Messina, Carmelo; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2017)
Ultrasound (US) of the hip is widely used both in children and adults for selected clinical indications. According to the European Society of Musculoskeletal Radiology, hip US is indicated for several clinical conditions involving the joint, soft tissues, and nerves. Hip US indications include fluid detection, synovitis, effusion, and synovial cysts; soft tissue evaluation such as tendinopathy and bursitis; and peripheral nerve pathology of large and small nerves around the hip. In addition, US is an effective imaging modality to guide interventional procedures. This article provides a brief overview of the US scanning technique of the hip and presents some common and less common conditions in which US of the hip is usually performed in adult patients.
Keywords: hip; ultrasound; joint; soft tissue; nerves; injections